Interpretation of military power in the context of realism paradigm - Žotkevičiūtė Banevičienė, Agnietė (Politologija, 2021)
The article seeks to reveal the possibilities of a theoretical interpretation of power in the broad sense and military power in the narrow sense in the context of the realism paradigm, with a deep focus on including intangible resources in the interpretation of power. In the article, the interpretation of power is consciously grounded on the synthesis of power as resources and power as relation perspectives meanwhile applying this synthesis to the analysis of military power. Thus, military power is perceived as covering not only material but also non-material resources and as being contextual in nature. The article forms assumptions that the interpretation of military power depends on the security environment perception of the political and military elite: by changing warfare concepts and force employment methods they introduce military innovations, while military doctrines are an instrument of power conversion – through them the security environment perception is imparted and the structure of military power is changed. Such an interpretation of military power, combining different insights based on the paradigm of realism, allows the formation of an alternative approach to the interpretation of military power.
Keywords: State power; military power; paradigm of realism; force employment; military resources